Hal- Hal Yang Ada Hubungannya Dengan Nilai Indeks Eritrosit Dengan Kadar Serum Feritin Pada Penyakit Anemia Di Laboratorium Patologik Klinik RS Dr. Tadjuddin Chalid Makassar Tahun 2022 - 2023 - Ganoko, Marwan Ahmad; Rahmat, Rezqiqah Aulia; Bamatraf, Anis (Barongko: Jurnal Ilmu Kesehatan, 2024)
Anemia is a medical condition characterized by low levels of hemoglobin in the blood, which can cause symptoms such as fatigue, dizziness, pale skin, and the body's inability to transport oxygen efficiently enough. Anemia can be caused by various factors, including iron deficiency, vitamin B12 deficiency, genetic disorders, and chronic diseases. Current research and data are also presented to provide a better understanding of the prevalence and impact of anemia in the global population. This research was conducted on 94 people suffering from anemia who were treated at RS Dr. Tadjuddin Chalid based on medical records from patients for the period January 2022 – June 2023. This research is a retrospective observational descriptive study of anemia patients from medical records treated at the hospital Dr. Tajuddin Chalid Makassar 2022 – 2023. Data analysis was processed using SPSS software. The results of this study show the distribution of anemia sufferers treated at RS Dr. Tadjuddin Chalid Makassar for the period January 2022 – June 2023, namely. Of the total sample of 94 people suffering from anemia, there were 47 male patients (50%) and 47 female patients (50%). Of the total samples based on age there were 94 samples, 39 people aged 0-5 years (Babies/Toddlers) (41.4%), 11 people aged 6-11 years (Children) (11.7%). ), those aged <60 years were 33 people (35.2%), and those aged >60 years (elderly/elderly) were 11 people (11.7%). The number of patients with normal MCV erythrocyte levels was 20 patients (21.2%) and 74 patients with abnormal MCV erythrocyte levels (78.8%). The number of patients with normal MCH erythrocyte levels was 27 patients (28.7%) and 67 patients with abnormal MCH erythrocyte levels (71.3%). The number of patients with normal MCHC erythrocyte levels was 56 patients (59.5%) and 38 patients with abnormal MCHC erythrocyte levels (40.5%). And the number of patients with normal ferritin levels was 42 patients (44.6%) and the number of patients with abnormal ferritin levels was 52 patients (55.4%).